A solid-reagent dispenser for use in the azocoll protease assay (and other insoluble substrate analyses). - G. E. Spady; J. R. Gresham; S. C. Simmons; F. H. Gaertner (Fungal Genetics Reports, 1980)
A solid-reagent dispenser for use in the azocoll protease assay (and other insoluble substrate analyses).